2007
DOI: 10.3354/dao076027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Neochlamydia-like bacterium associated with epitheliocystis in cultured Arctic charr Salvelinus alpinus

Abstract: Infections of branchial epithelium by intracellular gram-negative bacteria, termed epitheliocystis, have limited culture of Arctic charr Salvelinus alpinus. To characterize a bacterium associated with epitheliocystis in cultured charr, gills were sampled for histopathologic examination, conventional and immunoelectron microscopy, in situ hybridization, 16S ribosomal DNA (rDNA) amplification, sequence analysis and phylogenetic inference. Sampling was conducted at the Freshwater Institute (Shepherdstown, West Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 40 publications
3
56
2
1
Order By: Relevance
“…Epithelial hyperplasia, epithelial lifting along the lamellae, and lamellar fusion in the striped trumpeter were observed, although the filling of the interlamellar spaces was not as severe as that in previous reports. This differs from the nearly complete filling of the interlamellar spaces reported in both the largemouth bass (28) and the Arctic charr (15,27), which resulted in a severely compromised respiratory system. Striped trumpeter fish were recently reported to be affected by epitheliocystis (6).…”
Section: Simkania Negevensis Fr872582contrasting
confidence: 51%
See 2 more Smart Citations
“…Epithelial hyperplasia, epithelial lifting along the lamellae, and lamellar fusion in the striped trumpeter were observed, although the filling of the interlamellar spaces was not as severe as that in previous reports. This differs from the nearly complete filling of the interlamellar spaces reported in both the largemouth bass (28) and the Arctic charr (15,27), which resulted in a severely compromised respiratory system. Striped trumpeter fish were recently reported to be affected by epitheliocystis (6).…”
Section: Simkania Negevensis Fr872582contrasting
confidence: 51%
“…Epitheliocystis is now known to affect Ͼ80 different species of fish (7,10), and intriguingly, from all of these reports, it appears that the host responses considered to be severe or as having a hyperinfection are all from farmed fish (14)(15)(16)(27)(28)(29)(30)(31)(32). Molecular diagnostics confirmed that this CLO, from both cultured and wild sources, is a member of the order Chlamydiales, based on the Ͼ80% sequence similarity to other species in the order (18).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It is caused by Gram-negative bacteria, recently characterized as Chlamydia (Order: Chlamydiales), forming intracellular inclusions (Draghi et al 2007). These inclusions progressively enlarge, resulting in hypertrophied cells that resemble spherical cysts.…”
Section: Introductionmentioning
confidence: 99%
“…2). (Draghi et al, 2004(Draghi et al, & 2007Nowak and Lapatra, 2006;Polkinghorne et al, 2010). (Kranz, 1989;Wada et al, 1991;Wolke, 1992;Park and Huh, 1994;Montero et al, 1999;Wolf and Wolfe, 2005) Oh, 1999 &Sohn et al, 2000;Kim et al, 2008).…”
unclassified